2018
DOI: 10.1002/chem.201800285
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Length‐Dependent Formation of Virus‐Like Particles

Abstract: Understanding the assembly pathway of viruses can contribute to creating monodisperse virus-based materials. In this study, the cowpea chlorotic mottle virus (CCMV) is used to determine the interactions between the capsid proteins of viruses and their cargo. The assembly of the capsid proteins in the presence of different lengths of short, single-stranded (ss) DNA is studied at neutral pH, at which the protein-protein interactions are weak. Chromatography, electrophoresis, microscopy, and light scattering data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Sub-optimal length results in weak interactions while higher L c results in relatively irreversible reactions. The importance of L c value in SNA–polymer interactions was addressed in several articles [17,18,19,20]. Synthetic polymeric amines of various length and SNA of a fixed length have been explored in several earlier reports [17,18] but the set of amine chains investigated was restricted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub-optimal length results in weak interactions while higher L c results in relatively irreversible reactions. The importance of L c value in SNA–polymer interactions was addressed in several articles [17,18,19,20]. Synthetic polymeric amines of various length and SNA of a fixed length have been explored in several earlier reports [17,18] but the set of amine chains investigated was restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymeric amines of various length and SNA of a fixed length have been explored in several earlier reports [17,18] but the set of amine chains investigated was restricted. A recent work had investigated a set of SNA with varying chain length [19] and the minimal length of the SNA chain was determined as 14 nucleotides in reaction with virus particle of unknown chemical structure. A study of polylysine interaction with plasmid DNA [20] revealed that complexation occurred at 8 lysine units and an absence of interaction was observed with samples with 3 lysine units.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these techniques have improved capsid applicability as enzymatic delivery systems or nanoreactors, 2931 cargo-induced assembly exploiting small biologically relevant molecules such as oligonucleotides still represents a challenge and the crucial role of their length in particle assembly has already been established. 3234 In particular, while the electrostatic interaction between negatively charged cargo and the positively charged ARD of the N-terminus is guaranteed with long DNA or RNA molecules, shorter strands composed of few nucleotides showed to be less efficient in providing this stabilizing effect. In order to overcome this problem we here report on an innovative and versatile strategy for capsid stabilization exploiting the cross-linking agent DTSSP (3,3′-dithiobis(sulfosuccinimidylpropionate)).…”
Section: Introductionmentioning
confidence: 99%
“…Sub-optimal length results in weak interactions while higher Lc results in relatively irreversible reactions. The importance of Lc value in SNA -polymer interactions was addressed in several articles [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymeric amines of various length and SNA of a fixed length have been explored in several earlier reports [9,10] but the set of amine chains investigated was restricted. A recent work had investigated a set of SNA with varying chain length [11] and the minimal length of the SNA chain was determined as 14 nucleotides in reaction with virus particle of unknown chemical structure. A study of polylysine interaction with plasmid DNA [12] revealed that complexation occurred at 8 lysine units and an absence of interaction was observed with samples with 3 lysine units.…”
Section: Introductionmentioning
confidence: 99%